Scaling properties of the shear modulus of polyelectrolyte complex coacervates: A time-pH superposition principle - Tekaat, M.; Buetergerds, D.; Schoenhoff, M.; Fery, Andreas; Cramer, C. (Physical Chemistry Chemical Physics, 2015)
We analyze the scaling properties of pH-dependent shear modulus spectra of complex coacervates made of weak polyanions and strong polycations. For the first time, we report on a "time-pH superposition principle". This principle implies that the charge density in complex coacervates made of not fully charged polyions only influences the time scale of the relaxation dynamics, but not the mechanisms of the underlying dynamics.
CRIS-Team Scopus Importer:2023-03-20